CaZnO-based nanoghosts for the detection of ssDNA, pCRISPR and recombinant SARS-CoV-2 spike antigen and targeted delivery of doxorubicin. (November 2022) - Rabiee, Navid; Akhavan, Omid; Fatahi, Yousef; Ghadiri, Amir Mohammad; Kiani, Mahsa; Makvandi, Pooyan; Rabiee, Mohammad; Nicknam, Mohammad Hossein; Saeb, Mohammad Reza; Varma, Rajender S.; Ashrafizadeh, Milad; Zare, Ehsan Nazarzadeh; et al.
Abstract: Overexpression of proteins/antigens and other gene-related sequences in the bodies could lead to significant mutations and refractory diseases. Detection and identification of assorted trace concentrations of such proteins/antigens and/or gene-related sequences remain challenging, affecting different pathogens and making viruses stronger. Correspondingly, coronavirus (SARS-CoV-2) mutations/alterations and spread could lead to overexpression of ssDNA and the related antigens in the population and brisk activity in gene-editing technologies in the treatment/detection may lead to the presence of pCRISPR in the blood. Therefore, the detection and evaluation of their trace concentrations are of critical importance. CaZnO-based nanoghosts (NGs) were synthesized with the assistance of a high-gravity technique at a 1, 800 MHz field, capitalizing on the use of Rosmarinus officinalis leaf extract as the templating agent. A complete chemical, physical and biological investigation revealed that the synthesized NGs presented similar morphological features to the mesenchymal stem cells (MSCs), resulting in excellent biocompatibility, interaction with ssDNA- and/or pCRISPR-surface, through various chemical and physical mechanisms. This comprise the unprecedented synthesis of a fully inorganic nanostructure with behavior that is similar to MSCs. Furthermore, the endowed exceptional ability of inorganic NGs for detective sensing/folding of ssDNA and pCRISPR and recombinant SARS-CoV-2 spike antigen (RSCSA), along with in-situ hydrogen peroxide detection on the HEK-293 and HeLa cell lines, was discerned. On average, they displayed a high drug loading capacity of 55%, and the acceptable internalizations inside the HT-29 cell lines affirmed the anticipated MSCs-like behavior of these inorganic-NGs. Graphical abstract: Image 1 Highlights: The first inorganic-based nanoghosts with a similar performance same as the MSCs. Highly sensitive to ssDNA, pCRISPR, and SARS-CoV-2. Highly selective to SARS-CoV-2 in different environments. Innovative, green, and cost-effective method to prepare an optical nano-probe for the SARS-CoV-2 detection.